Sinagoga Abandonada: história, etnicidade e identidade judaica em Nilópolis RJ - Soares, Hebert Quaresma (2014)
The problematics of research emanates from the relationship between the current state of abandoned Synagogue Tiferet Israel and the Jewish Diaspora of Nilópolis culminating in the extinction of the community that at its peak reached total approximately three hundred Jewish families. From a technical standpoint, there was data collection through literature, documentary, interviews, life stories and, notably, participant observation. Drew up a historical line of the immigration flow of Jews originate from Eastern Europe, focusing on Poland, the country of origin of most who settled in Nilópolis and comparing the motives that caused the Jewish diasporas of Poland and of Nilópolis, we can understand a contextual paradox, in that pursuit and poverty, in this freedom and prosperity. Finally, it was concluded, that the Jewish ethnicity, which seemed deserted, before the picture of the defunct community and abandoned synagogue, still alive in the city by jewish cemetery.